LITERATURE REVIEW: CHATGPT SEBAGAI MEDIUM KOLABORATIF UNTUK OPTIMALISASI PEMBELAJARAN BAHASA ARAB - Marwaji Deden (STIT Darul Hijrah Martapura, 2025)
This literature review analyzes the use of Artificial Intelligence, specifically ChatGPT, as a collaborative medium to optimize Arabic language learning in Madrasah Aliyah (Islamic Senior High School). This study aims to identify the effectiveness, opportunities, and challenges in integrating ChatGPT into the learning process. The results of the study indicate that ChatGPT enhances learning interactivity through real-time feedback, personalized material presentation, and adaptive support for listening, speaking, reading, and writing skills. Furthermore, ChatGPT encourages the creation of a learner-centered learning environment by actively and independently engaging learners. However, challenges such as linguistic accuracy, limited digital teacher literacy, and infrastructure readiness remain obstacles to its implementation. This study confirms that ChatGPT has strong potential as a pedagogical tool and collaborative partner in learning. Its strategic integration requires instructional supervision, ethical considerations, and adequate technological readiness. This study has implications for the development of AI-based learning designs and digital collaborative models in the future.